ANALYSIS OF ECONOMIC EFFICIENCY IN THE FORMATION OF CONCRETE PRODUCTS IN NEW VIBRATING PLATES - Pshinko, O. M.; Lohvynenko, Ye. O.; Shchipanova, Ye. V.; Buriak, Ye. Yu. (Science and Transport Progress, 2007)
The analysis of economic efficiency of a new vibrating platform is brought, allowing due to optimization of a dynamic mode of fluctuations to reduce direct expenses for let released production of ferro-concrete on cement, pair, the electric power. The estimation of efficiency of investments on introduction of vibrating platforms in view of the recommendations developed UNCTAD is given also.